2018
DOI: 10.1017/s1049023x18000109
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Pediatric Physiological and Anatomical Triage Score in Mass-Casualty Incident

Abstract: The accuracy of PPATS was superior to other methods for secondary triage of children. Toida C , Muguruma T , Abe T , Shinohara M , Gakumazawa M , Yogo N , Shirasawa A , Morimura N . Introduction of pediatric physiological and anatomical triage score in mass-casualty incident. Prehosp Disaster Med. 2018;33(2):147-152.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Some hospitals apply primary triage protocols, such as simple triage and rapid treatment (START), for secondary triage; however, understandably, they perform poorly in this setting. 44 Duplicating primary triage in hospital is not only unlikely to be effective for achieving the different objectives of secondary triage but also highly inefficient and fails to take into account the additional information available on which to base a secondary triage decision. In most situations, secondary triage is conducted by a single senior physician or surgeon or group of senior physicians or surgeons drawn from a variety of backgrounds, including emergency medicine, intensive care, or trauma surgery.…”
Section: Secondary Triagementioning
confidence: 99%
See 1 more Smart Citation
“…Some hospitals apply primary triage protocols, such as simple triage and rapid treatment (START), for secondary triage; however, understandably, they perform poorly in this setting. 44 Duplicating primary triage in hospital is not only unlikely to be effective for achieving the different objectives of secondary triage but also highly inefficient and fails to take into account the additional information available on which to base a secondary triage decision. In most situations, secondary triage is conducted by a single senior physician or surgeon or group of senior physicians or surgeons drawn from a variety of backgrounds, including emergency medicine, intensive care, or trauma surgery.…”
Section: Secondary Triagementioning
confidence: 99%
“…In most situations, secondary triage is conducted by a single senior physician or surgeon or group of senior physicians or surgeons drawn from a variety of backgrounds, including emergency medicine, intensive care, or trauma surgery. 28,[45][46][47] Toida and colleagues 44 developed the Pediatric Physiological and Anatomical Triage Score specifically for pediatric secondary triage for trauma and CBRNE (chemical, biological, radiological, nuclear, and explosive) -related disasters. Pneumonia severity scores 48,49 have been investigated for secondary triage in pandemics but found to perform poorly.…”
Section: Secondary Triagementioning
confidence: 99%
“…In terms of priority, patients with scores ≥six points were classified as "immediate." 9 In contrast, TRTS was based on RR, sBP, and GCS, with 12 being the highest possible score. Patients with scores between one to 10 points were assigned "immediate" priority ( Table 1).…”
Section: Criteria Of the Ppats And Trtsmentioning
confidence: 99%
“…[4][5][6][7][8] Previous study showed that the Pediatric Physiological and Anatomical Triage Score (PPATS) was developed as a new secondary triage method, with a scoring system for children in a disaster setting, since secondary triage is critical for refining the results of primary triage. 9 Because the previous study was a single-center study, this study was conducted as a multi-center study using data from the national registry of Japan. The aim of this study was to externally validate the PPATS for severe trauma patients, of whom will be the majority in disaster settings.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, The article by Takashi Muguruma, et al is inspiring. 1 It compared a triage system designed for pediatric patients, Pediatric Physiological and Anatomical Triage Score (PPATS), with a widely used triage method for generic patients, Triage Revised Trauma Score (TRTS), 2 and suggested that PPATS is a viable and useful triage method specifically for pediatric patients. 1 However, different disasters have their own characteristics of casualties.…”
mentioning
confidence: 99%